Leaf micromorphology, antioxidative activity and a new record of 3-deoxyamphoricarpolide of relict and limestone endemic Amphoricarpos elegans Albov (Compositae) from Georgia - Gavrilović, Milan; Tešević, Vele; Đorđević, Iris; Rajčević, Nemanja; Bakhia, Arsena; Garcia Jacas, Núria; Susanna, Alfonso; Marin, Petar D.; Janaćković, Peđa (Archives of Biological Sciences, 2018)
Paper description: This is a first report on the micromorphology and phytochemical and biological activity investigations of the rare and stenoendemic Amphoricarpos elegans Albov (Compositae) from Georgia. We detected the presence of glandular trichomes on leaves, we identified and characterized 3-deoxyamphoricarpolide, a known sesquiterpene lactone for this genus, and we examined the antioxidative activity of leaf extracts obtained using a Soxhlet apparatus. With regard to the chemotaxonomic significance of amphoricarpolides, this compound represents a link between Balkan and Caucasian species of the same genus. The considerable antioxidative potential points to its possible pharmacological and medical applications. Abstract: We examined for the first time the leaf micromorphology, phytochemistry and biological activity of the rare and stenoendemic Amphoricarpos elegans Albov (Compositae) from Georgia. Scanning electron microscopy (SEM) revealed the presence of glandular trichomes on the leaves, which appeared as glandular dots that are considered the main sites of biosynthesis and accumulation of sesquiterpene lactones. Using high-performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) spectroscopy analyses, we identify and characterized 3-deoxyamphoricarpolide, a known sesquiterpene lactone for the genus Amphoricarpos Vis. Regarding chemotaxonomic significance, 3-deoxyamphoricarpolide represents a link between Balkan and Caucasian species of the genus. The antioxidative capacity of different leaf extracts, obtained using a Soxhlet extractor, was evaluated by two radical scavenging assays: DPPH (1,1-diphenyl-2-picrylhydrazyl) radical and the 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS), and ferric ion reducing antioxidant power (FRAP). The total phenolic and flavonoid contents were also determined. The highest antioxidative activity and the highest phenolic and flavonoid contents were detected in the methanol fraction, as a result of the contribution of not only phenols, but probably also lactones. The considerable antioxidative potential indicates possible applications in pharmacy and medicine. https://doi.org/10.2298/ABS180309022G Received: March 9, 2018; Revised: May 5, 2018; Accepted: May 14, 2018; Published online: June 4, 2018 How to cite this article: Gavrilović M, Tešević V, Đorđević I, Rajčević N, Bakhia A, Garcia Jacas N, Susanna A, Marin PD, Janaćković P. Leaf micromorphology, antioxidative activity and a new record of 3-deoxyamphoricarpolide of relict and limestone endemic Amphoricarpos elegans Albov (compositae) from Georgia. Arch Biol Sci. 2018;70(4):613-20.